The Influence of The Talking Stick Learning Model on Student Learning Outcomes Theme 2 Unity in Difference Class VI SDN 091607 Sinaksak - Tri Aprilla Banjarnahor; Lisbet Novianti Sihombing; Desi Sijabat (MultiTech Publisher, 2023)
This research aims to determine the INFLUENCE OF THE TALKING STICK LEARNING MODEL ON STUDENT LEARNING OUTCOMES THEME 2 UNITY IN DIFFERENCE CLASS VI STATE 091607 SINAKSAK PRIMARY SCHOOL, the method in this research is a quantitative experimental type method whose research design form is pre-experimental type one group pretest-posttest. The population and sample used were saturated sampling with 24 samples, as well as two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of the talking stick model. The data collection technique is the test technique. Test results using the t-test technique with the help of the spss program, based on the results of calculating the significant value (2-tailed) < 0.05, namely 0.000 < 0.05, tcount > ttable = 22.859 > 2.064, H0 is rejected and Ha is accepted. So it can be concluded that there is an influence of the Talking stick learning model on the learning outcomes of class VI students in theme 2 unity in differences subtheme 1 harmony in differences in class VI SD Negeri 091607 Sinaksak